Screening of the Pandemic Response Box identifies anti-microsporidia compounds. - Qingyuan Huang; Jie Chen; Guoqing Pan; Aaron W Reinke (Public Library of Science (PLoS), 2023)
Microsporidia are fungal obligate intracellular pathogens, which infect most animals and cause microsporidiosis. Despite the serious threat that microsporidia pose to humans and agricultural animals, few drugs are available for the treatment and control of microsporidia. To identify novel inhibitors, we took advantage of the model organism Caenorhabditis elegans infected with its natural microsporidian Nematocida parisii. We used this system to screen the Pandemic Response Box, a collection of 400 diverse compounds with known antimicrobial activity. After testing these compounds in a 96-well format at high (100 μM) and low (40 μM) concentrations, we identified four inhibitors that restored the ability of C. elegans to produce progeny in the presence of N. parisii. All four compounds reduced the pathogen load of both N. parisii and Pancytospora epiphaga, a C. elegans-infecting microsporidia related to human-infecting species. One of these compounds, a known inhibitor of a viral protease, MMV1006203, inhibited invasion and prevented the firing of spores. A bis-indole derivative, MMV1593539, decreased spore viability. An albendazole analog, MMV1782387, inhibited proliferation of N. parisii. We tested albendazole as well as 5 other analogs and observed that MMV1782387 was amongst the strongest inhibitors of N. parisii and displayed the least host toxicity. Our study further demonstrates the effectiveness of the C. elegans-N. parisii system for discovering microsporidia inhibitors and the compounds we identified provide potential scaffolds for anti-microsporidia drug development.